The economic impact of wellness tourism with a focus on the spa industry in the Czech Republic - Smrčka, Pavel (2016)
This master thesis aims to provide a complex up-to-date overview of the spa industry in the Czech Republic and to analyze the position of Spa Luhačovice. Having shown the growing global importance of wellness tourism, the focus moves onto the spa industry which plays a major role in wellness. Nevertheless,the medical significance of spas can't be overlooked, especially in the Czech Republic where spas are known for the quality of medical care. While statistical reports from the Health Information and Statistics of the Czech Republic and from the Czech Statistical Office are being examined and analyzed in the country's perspective, Global Wellness Institute provides the majority of the global wellness and spa data. The thesis shows the current state of the industry in the country with its strengths and weaknesses. Moreover, the practical part is focused on Spa Luhačovice, the biggest spa in Moravia region. Various information and data are compared to overall development of the spa industry in the country. Finally, an interview with the spa representative is conducted to further clarify the findings of this thesis.